STRATEGI PRAGMATIK BAHASA HUMOR DALAM ACARA “MARIO TEGUH GOLDEN WAYS” DI METRO TV - Enie Hendrajati (JURNAL SOSIAL HUMANIORA (JSH), 2017)
Speech humor in MTGW program is assumed as a "good practice" of pragmatic strategy to entertain, inspire and motivate audience. The focus and objective of this study is to get a description of the pragmatic strategy of harmonizing word choice, sentence, and humorous language in MTGW program. How pragmatic strategies have implications for the use of words, sentences, and language styles so that the audience feel entertained and laughed.This research uses desciptive qualitative approach. Data in the form of humorous languages is collected by listening and recording. The method of analysis is padan and agih. The word data, sentence, and style of the humorous language are linked and compared to other words, sentences, and language styles in terms of humorous sense between sentences produced and comparator sentences. As a result, the pragmatic strategy MT uses in the MTGW program on Metro TV is to harmonize between lingual units of words, sentences, and language styles with humor and courtesy. MT uses a locusive and illocusive strategy with humorous tones and politeness in choosing, organizing and producing every word, sentence, and style of humor. Through the choice of words, sentences, and language style, the MT uses pragmatic strategies in conveying his message as a motivator and the perlocutionary effect is that the audience becomes interested or entertained.